The Translation Errors in the Translation of the Qur'an in Indonesian into Arabic on AI Poe - Framesthia, Luthfi Mustika; Ulpah, Siti Marya; Aziz, Riza Abdul; Novia, Tria; Al Farisi, Mohamad Zaka; Supriadi, Rinaldi (Study Program of Arabic Language Teaching, 2025)
This research aims to determine and classify the forms of morphological, syntactic, and semantic errors resulting from AI Poe's translation in translating the translated text of the Al-Qur'an. By applying descriptive qualitative research methods and a literature study research design, this research will reveal the forms of translation errors. The data was obtained from the results of AI Poe's translation of the verses of the Koran that appeared in the book Exemplary Stories of Muslim Children by Maulana Ar-Rosyid. The analysis is conducted through three main steps: identifying linguistic errors, classifying errors based on morphological, syntactic, and semantic aspects, and analyzing and interpreting the errors about the limitations of AI Poe and the complexity of the text. The validity of the data is strengthened through source triangulation, which involves comparing it with Arabic dictionaries, linguistic theories, and expert opinions on translation. The research results concluded that AI Poe had significant limitations in translating the translated text of the Al-Qur'an from Indonesian to Arabic. Of all the data translated by AI Poe, 58% was indicated to contain errors. From the analysis of 21 existing text data, several linguistic errors were found spread across three main aspects: namely syntactic 34 errors (51%), semantic 25 errors (37%), and morphological eight errors (12%).